Endocrine Regulation Of Metabolism During Fasting And Feeding; Comparative Analysis Of Hormonal Control Mechanisms (Journal of Pharmaceutical Negative Results, 2022)
Background: The endocrine system controls the metabolic rate during starvation and feeding by insulin, glucagon, and cortisol. Such hormones maintain energy levels and the body’s equilibrium by regulating glucose, fats, and protein consumption.Objectives: To examine and compare the hormonal control mechanisms of metabolism during fasting and feeding.Study design: A cross-sectional study.Place and duration of study: Margalla Institute of Health Sciences, Rawalpindi. From January 2021 to June 2021.Methods: In the present study 150 patients were taken under controlled fasting and feeding conditions. Blood samples were taken to determine the levels of insulin, glucagon, and cortisol. An analysis of variance with the use of standard deviation and p-values was used to compare the hormonal responses of the two states.Results: There was a significant rise in the fed-state insulin levels to 130% (SD = 0. 25; P < 0. 01) the fasting levels and a significant decrease in the fed-state glucagon levels to 80% (SD = 0. 18; P < 0. 01) of the fasting level. Cortisol was shown to have increased by 35% (SD =0. 30, p< 0. 01) in the fasting measurements while glucagon increased by 25% (SD = 0. 22, p< 0. 01). These results help to point at the existence of considerable hormonal variation between the periods of fasting and feeding.Conclusion: The study proves that insulin is predominant d uring feeding because it helps in the storage of nutrients while glucagon and cortisol are more active during fasting as they aid in mobilization of energy. Knowledge of these mechanisms is vital in the regulation of metabolic health to control diseases such as diabetes and obesity.